2010
DOI: 10.1158/1078-0432.ccr-09-3342
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Methylated Genes in Normal Prostate Tissues from African American and Caucasian Men

Abstract: Purpose: Aberrant DNA methylation changes are common somatic alterations in prostate carcinogenesis. We examined the methylation status of six genes in prostate tissue specimens from African American (AA) and Caucasian (Cau) males.Experimental Design: We used pyrosequencing to quantitatively measure the methylation status of GSTP1, AR, RARβ2, SPARC, TIMP3, and NKX2-5. Real-time PCR was used to determine gene expression, and gene reactivation was analyzed by 5-aza-2′-deoxycytidine and/or trichostatin A treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 23 publications
5
112
0
Order By: Relevance
“…Additional logistic regression analysis of our data suggests that the difference in specificity can be correlated, in part, with subject age and ethnicity. This is intriguing, as it has been previously reported that DNA methylation patterns for some genes depend on both subject age and ethnicity (33 ).…”
Section: Discussionmentioning
confidence: 86%
“…Additional logistic regression analysis of our data suggests that the difference in specificity can be correlated, in part, with subject age and ethnicity. This is intriguing, as it has been previously reported that DNA methylation patterns for some genes depend on both subject age and ethnicity (33 ).…”
Section: Discussionmentioning
confidence: 86%
“…The studies that involved unbiased screening by gene expression analysis have shown SPARC expression to be correlated with high-grade, androgen-resistant, and metastatic disease. In addition, SPARC was shown previously to attract prostate cancer cells into bone by promoting a migratory and invasive phenotype (39 -42 (48) have shown that SPARC is silenced by promoter methylation in African-American patients who often develop aggressive prostate cancer with 2-fold higher mortality rate than Caucasian American patients (48). The apparent disagreement between these studies may be due to multiple factors, including expression profiling of the primary tumor, batch variability, and lack of clinical data for the site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…9 These results are supported by differences in the specific methylation of genes such as GSTP1, AR, RAR beta2, SPARC, TIMP3 and NKX2-5 in which higher methylation was found in African-Americans than in Caucasian-Americans. 10 The methylation differences found in adulthood could potentially be contributed by neonatal imprinting, as demonstrated in our early studies where we showed that both the growth of sex steroid-sensitive organs and their steroidmetabolizing enzymes in the target organs were affected by prior exposure of animals to testosterone or 17-b-estradiol during the neonatal period. [11][12][13] In addition to the report cited above characterizing racial/ethnic differences in prostate cancer among AfricanAmericans, Caucasian-Americans, Chinese and Japanese, numerous other attempts have been made to characterize the differences among Americans, Europeans, Africans and other Asian races.…”
mentioning
confidence: 74%